Analysis of Diamond Fraud and Individual Morality on Village Fund Fraud - Sufiati, Sufiati; Sambo, Eva Marin; Pura, Rahman (Economics, Business, Accounting & Society Review, 2024)
This study investigates the key drivers of village fund fraud, expanding on the established fraud diamond model. Conducted in the Patallasang sub-district of Gowa Regency, the research surveyed 51 village government officials to analyze the influence of pressure, opportunity, rationalization, capabilities, and individual morality on fraudulent activities related to village funds. The results reveal that pressure, opportunity, and rationalization have significant positive effects on village fund fraud, while capabilities and individual morality exert significant negative influences. Individual morality emerges as the most dominant factor in determining the occurrence of village fund fraud. This study contributes to the theoretical development of the fraud diamond framework by incorporating individual morality as a critical causal element in understanding fraud within the village fund context. The findings of this study hold important implications for policymakers and local government authorities tasked with mitigating fraud and ensuring the effective utilization of village funds. By addressing the multifaceted drivers identified, targeted interventions can be designed to strengthen governance, promote ethical decision-making, and safeguard the integrity of village-level financial management.